2017
DOI: 10.1111/inr.12392
|View full text |Cite
|
Sign up to set email alerts
|

Stressors affecting nursing students in Pakistan

Abstract: The fact that scores on the Stressors in Nursing Students scale increased over 4 years of the programme and males scored higher than females should alert nursing schools and policymakers related to nursing education and workforce to pay attention to prevent attrition from nursing programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
2
16
0
2
Order By: Relevance
“…Previous published studies on the original English version and translations – and some in the process of being published – provide a range of solutions for PCA of the SINS. These range from no apparent structure [8] to an almost identical structure to the original English version. In the present study we found that the simplest structure had a factor structure with some similarities and differences to the original English version.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous published studies on the original English version and translations – and some in the process of being published – provide a range of solutions for PCA of the SINS. These range from no apparent structure [8] to an almost identical structure to the original English version. In the present study we found that the simplest structure had a factor structure with some similarities and differences to the original English version.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when the SINS was developed, and exploratory factor analysed, these four dimensions were apparent: academic; clinical; financial; and confidence [2] and this structure has been observed in a cohort of Hong Kong nursing students [1], using the English version and also in a version of SINS translated into Chinese and used in China Mainland [7]; a sample which was also confirmatory factor analysed. However, a Chinese version adapted for use in Taiwan and used with a cohort of nursing students in Taiwan showed no apparent underlying structure (Unpublished results) and the same phenomenon has appeared in a version translated into Urdu and used with a cohort of nursing students in Pakistan [8]. Clearly, it is important to continue to translate and study the SINS in different populations and in different languages as the structures may provide insight into how stressors in nursing students are perceived in different countries and in different cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan çalışmada kız öğrencilerin stres düzeyinin erkek öğrencilere göre daha yüksek olduğu görülmüştür (p<0,001). Yurt dışında yapılan çalışma sonuçları incelendiğinde, hemşirelik öğrencilerinde cinsiyet ile stres düzeyi arasında anlamlı farklılık olmadığını gösteren çalışma bulgularına rastlanmakla beraber 19,21 Watson ve arkadaşları (2017) tarafından Pakistan'lı hemşirelik öğrencileri ile yapılan çalışmada erkek öğrencilerin stres düzeyinin daha yüksek olduğu görülmüştür 27 . Yıldırım ve arkadaşlarının (2016) hemşirelik öğrencileri ile yaptığı çalışmada da kız öğrencilerin stres düzeylerinin daha yüksek olduğu görülmüştür 25 .…”
Section: Discussionunclassified
“…Ölçeğin akademik ve uygulama stresi olmak üzere 2 alt boyutu bulunmaktadır. Uygulama stresi alt boyutu 4,5,7,9,11,13,15,16,18,19,21,24,25,27,29…”
Section: Kişisel Bilgi Formuunclassified
“…Pakistani nurses, like nurses in other developing countries, are subjected to various workplace issues including workplace violence (Ali & Naylor, ; Jafree, ), long working hours (Kim & Motsei, ), inflexible work schedules (Yasir & Majid, ), work‐life balance issues (AlAzzam, AbuAlRub, & Nazzal, ; Yasir, Majid, Yasir, & Khan, ), unattractive remunerations (Atefi, Abdullah, & Wong, ) and heavy workload (MacPhee, Dahinten, & Havaei, ). Not to mention that they have to deal with anxious patients, worried relatives and stressed colleagues (Rehman & Ali, ; Watson, Rehman, & Ali, ). All these issues negatively affect performance of nurses and contribute to depression, anxiety, stress (Rathnayake & Ekanayaka, ), burnout (Khamisa, Oldenburg, Peltzer, & Ilic, ), poor health (Mooring, ) and low performance (Javed, Yasir, Majid, Shah, et al, ).…”
Section: Introductionmentioning
confidence: 99%